Medical implications of biofilms - Wilson, Michael 1947 April 12-; Devine, Deirdre 1961- (Cambridge University Press, 2003)
Human tissues often support large, complex microbial communities growing as biofilms that can cause a variety of infections. As a result of an increased use of implanted medical devices, the incidence of these biofilm-associated diseases is increasing: the non-shedding surfaces of these devices provide ideal substrata for colonisation by biofilm-forming microbes. The consequences of this mode of growth are far-reaching. As microbes in biofilms exhibit increased tolerance towards antimicrobial agents and decreased susceptibility to host defence systems, biofilm-associated diseases are becoming increasingly difficult to treat. Not surprisingly, therefore, interest in biofilms has increased dramatically. The application of microscopic and molecular techniques has revolutionised our understanding of biofilm structure, composition, organisation, and activities, resulting in important advances in the prevention and treatment of biofilm-related diseases. The purpose of this book, which was first published in 2003, is to bring these advances to the attention of clinicians and medical researchers